Reputasi perusahaan keluarga: Accrual dan real earnings management - William Sebastian Tanusaputra; Rizky Eriandani (STIE Perbanas Surabaya, 2020)
This study examined the effect of earnings management on reputation in family firms listed on the Indonesia Stock Exchange (ISE). The data were collected from audited financial reports of companies listed on the Indonesia Stock Exchange for 2017-2019. The data were slected by using a purposive sampling towards 264 companies. The data of company reputation comes from the corporate image reward website, and they were analyzed using logistic regression. The results showed there is no effect of accrual earnings management (AEM) on the family firms’ reputation. On the contrary, real earnings management (REM) has a significant negative effect on family firms. This result implies that earnings manipulation by adjusting the company’s operations will result in a bad reputation.